Тривимірний нелокальний квантовий вакуум як джерело фотонів - Fiscaletti, D.; Sorli, A. (Publishing house "Academperiodika", 2020)
A model of a three-dimensional quantum vacuum defined by the processes of creation/annihilation of quanta corresponding to elementary energy density fluctuations is proposed. In it, a photon is not a primary physical reality but emerges itself as a special state of the three-dimensional quantum vacuum. In this model, the three-dimensional quantum vacuum has a ground state which acts as a “cosmic reservoir” of photons, which emits and absorbs photons and Planck’s law of the spectral distribution of the energy radiated by a black body derives from the fundamental processes in the three-dimensional quantum vacuum, in particular, in the context of a quantization volume responsible for the appearance of photons. Finally, the idea of the Lamb shift of hydrogenoid atoms as a phenomenon determined by the ground state of the quantum vacuum which acts as a reservoir of photons is explored.